(3GdSNQjI ai GdCOH GdYQHi GdMOjKs (3YHO GdYRjR GdHTQi fehPLGs - (3GdSWhMi(B, (3SgG YHO GdSJGQs ((3GdbGgQIs (3GdgjFI GdeUQjI GdYGeI ddcJGHs, 2007)
(3jeKd egeI gPG GdcJGH bjeI ai MjGJfG GdjhejI dGQJHGWg HGdSNQjIs
hurg
5
Keywords: (3GdSNQjI ai GdCOH GdYQHis